2019
DOI: 10.1136/bcr-2018-229178
|View full text |Cite
|
Sign up to set email alerts
|

Diplopia and proptosis due to isolated lateral rectus plasmacytoma in a patient with multiple myeloma

Abstract: Orbital involvement of multiple myeloma (MM) is uncommon, with most of those reported cases occurring at the time of initial diagnosis of MM. We present a case of an extramedullary plasmacytoma involving only the right lateral rectus of a patient who had been in disease remission. The patient presented with new-onset diplopia and an abduction deficit of the right eye, with mild proptosis. In light of her past medical history of MM, an orbital MRI was obtained. The MRI demonstrated an isolated finding of eccent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Literature review identified a total of 111 previously reported cases in 68 articles regarding orbital involvement in patients with systemic MM (Table 2). 4,6-61…”
Section: Resultsmentioning
confidence: 99%
“…Literature review identified a total of 111 previously reported cases in 68 articles regarding orbital involvement in patients with systemic MM (Table 2). 4,6-61…”
Section: Resultsmentioning
confidence: 99%
“…EOMs are usually affected in combination with adjacent soft tissue or bone. To date, isolated involvement of EOM has been reported in 3 patients [ 7 , 15 , 16 ]. Whether isolated or in combination with other tissues, the hematogenous spread of neoplastic plasma cells could result in extramedullary involvement of EOM [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMD affecting EOM is a relatively rare phenomenon. Studies reporting EOM involvement in MM are summarized in Table 1 [7][8][9][10][11][12][13][14]. EOMs are usually affected in combination with adjacent soft tissue or bone.…”
Section: Case Reports In Ophthalmologymentioning
confidence: 99%
“…They can involve the orbit, conjunctiva [ 7 ], uvea, retina, lacrimal sac [ 8 ], and ciliary body. They present as an orbital mass, epibulbar mass [ 9 ], orbital abcess [ 6 ], chalazion [ 6 ], dacryocystitis [ 6 ], granulomatous uveitis or as an isolated mass in the rectus muscles [ 4 , 10 ]. An increase in the IOP or neovascular glaucoma has also been reported in the iris and ciliary body plasmacytomas [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…They may originate from the bone when involving the orbit [ 2 ] and can mimic other ocular neoplasms such as lymphoma, metastases, chondrosarcoma, or giant cell tumors [ 3 ]. Plasmacytomas of the orbit can present with diplopia, proptosis [ 4 ], and symptoms of orbital cellulitis as well. They may show unspecific imaging characteristics and may not be distinguished from other ocular tumors which would make their diagnosis more difficult [ 3 ].…”
Section: Introductionmentioning
confidence: 99%